Aortic Arch Hypoplasia in Infants: Algorithm of Diagnosis and Treatment - I. Truba (Український журнал серцево-судинної хірургії, 2020)
Background. Aortic arch hypoplasia is a congenital anomaly of the development of the aortic arch characterized by hemodynamically significant narrowing of one or more segments of the aortic arch. Despite the great interest in the problem of aortic arch hypoplasia, there are many contradictions in terms of terminology and classification. It is quite difficult to draw a clear line between normal physiology and pathology to determine in which cases there is a true hypoplasia, so, from a practical standpoint, the fundamental issue is the selection of criteria with reference to which we can talk about clinically and prognostically significant aortic arch hypoplasia. Important and yet controversial are the issues of multi-stage treatment of aortic arch hypoplasia and concomitant congenital heart diseases (CHD), and, in case of the isolated variant of hypoplasia, the choice of surgical approach.